Kepemimpinan Kepala Sekolah sebagai Motivator: Upaya Meningkatkan Kinerja Guru - Abdul Majid, M. Ayi (Universitas KH. Abdul Chalim Pacet Mojokerto, 2024)
This research was conducted at S.M.A.N. 1 Gondang using qualitative research methods and a case study approach. Research subjects included school principals, deputy principals for curriculum, and teachers. Data was collected through observation, interviews, and documentation, and data analysis was performed using the triangulation method. This research aims to identify the role of the principal as a motivator and strategies used to improve teacher performance at S.M.A.N. 1 Gondang. Apart from that, this research also aims to understand how this role can influence the quality of teaching and the effectiveness of learning in schools. The research results show that the principal acts as a motivator by making himself part of the school's